Transient Stability Analysis of Grid-connected Wind Turbines with Time Domain Simulation - Hongwei Li; Haiying Dong; Shuaibing Li; Linxin Cao (Institute of Advanced Engineering and Science, 2014)
With an ever-increasing pentration of wind power into power system, the influence to overall system behavior and stability becomes obviously. Therefore, it is so necessary to require wind turbines have good grid adaptability. This paper investigates the effect ofdirectly grid-connectedfront-end speed controlled wind turbines (FSCWT) on transient stability of power system.For this purpose, a voltage based synchronous generator model is used and the drive train model with WinDriver is built. By using a fast excitation control of FSCWT exciter, the FSCWT wind turbines can successfully ride through grid fault and have no problem of angular stability when connected to grid. Simulation studies are carried out to demonstrate and compare the transient performance of the IEEE 5-machine 14-bus system with FSCWT replace by double fed induction generators (DFIG) during a three phase fault. Results show that a better transient stability performance is achieved with an intergration of FSCWT in comparsion with DFIG, which can even bring some benefits on power system transient performance and stability.DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3331